Edukasi Keamanan Digital dan Etika Bermedia Sosial bagi Remaja Sekolah - Saeful Anwar; Tati Supra; Indah Ratna Ningsih; Kevin Salsabil Arlandy (AMMA : Jurnal Pengabdian Masyarakat, 2022)
In today's digital age, social media use has become an integral part of teenagers' lives. However, increased access to information and online communication also brings new challenges, especially in terms of digital safety and media etiquette. School adolescents, as active users of social media, often lack an adequate understanding of the risks that can arise from their digital activities. This study aims to provide a comprehensive understanding of the importance of digital safety and the application of ethics in social media among teenagers. The method used is a literature study combined with an educational approach based on learning and training modules. The results of the study show that most teenagers are not aware of the importance of personal data protection, password security, and the risk of spreading false information or hoaxes. In addition, the lack of ethics in communicating on social media can lead to social conflicts and privacy violations. Therefore, a systematic educational approach is needed to equip teenagers with the knowledge and skills to maintain digital security and act ethically in the digital space. This educational effort needs to involve the role of teachers, parents, and school policies that support digital literacy as a whole.